Cultural Phenomena Believed to Be Associated With Orthorexia Nervosa – Opinion Study in Dutch Health Professionals - Syurina, Elena V.; Bood, Zarah M.; Ryman, Frida V. M.; Muftugil-Yalcin, Seda (Frontiers in Psychology, 2018)
Orthorexia Nervosa (ON) is a newly coined eating pattern which disproportionately affects Western countries. Research on the matter is scarce. This study aimed to investigate how Dutch (mental) health professionals evaluate the influence of “Western culture” on development of ON. This mixed methods study included interviews (n=15) and a questionnaire (n=157). The extent of influence of the “Western culture” was suggested to be quite high: score 74 out of 100. Among the phenomena believed to affect Orthorexia were: societal transitions (epidemiological and welfare) and cultural ideas (body ideal and control over life) which are influenced by the internet and media spread. In addition it was noted that ON is unique among eating disorders since it does not carry negative connotations of anorexia or obesity associated with “losing control”. The findings suggest that “Western culture” contributes to the establishment of a high risk environment for development of behaviours associated with ON.